Booster dose of mRNA vaccine augments waning T cell and antibody responses against SARS-CoV-2 - Özbay Kurt, Feyza Gül; Lepper, Alisa; Gerhards, Catharina; Römer, Mathis; Lasser, Samantha; Arkhypov, Ihor; Bitsch, Rebekka; Bugert, Peter; Altevogt, Peter; Gouttefangeas, Cécile; Neumaier, Michael; Utikal, Jochen; et al. (Frontiers in immunology, 2022)
A gradual decay in humoral and cellular immune responses over time upon SAR1S-CoV-2 vaccination may cause a lack of protective immunity. We conducted a longitudinal analysis of antibodies, T cells, and monocytes in 25 participants vaccinated with mRNA or ChAdOx1-S up to 12 weeks after the 3rd (booster) dose with mRNA vaccine. We observed a substantial increase in antibodies and CD8 T cells specific for the spike protein of SARS-CoV-2 after vaccination. Moreover, vaccination induced activated T cells expressing CD69, CD137 and producing IFN-γ and TNF-α. Virus-specific CD8 T cells showed predominantly memory phenotype. Although the level of antibodies and frequency of virus-specific T cells reduced 4-6 months after the 2nd dose, they were augmented after the 3rd dose followed by a decrease later. Importantly, T cells generated after the 3rd vaccination were also reactive against Omicron variant, indicated by a similar level of IFN-γ production after stimulation with Omicron peptides. Breakthrough infection in participants vaccinated with two doses induced more SARS-CoV-2-specific T cells than the booster vaccination. We found an upregulation of PD-L1 expression on monocytes but no accumulation of myeloid cells with MDSC-like immunosuppressive phenotype after the vaccination. Our results indicate that the 3rd vaccination fosters antibody and T cell immune response independently from vaccine type used for the first two injections. However, such immune response is attenuated over time, suggesting thereby the need for further vaccinations.
Gesehen am 14.08.2023